Time spent on treatment (TSOT). An independent assessment of disease severity in atopic dermatitis - Jemec, Gregor B.E. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Introduction: Time spent on treatment (TSOT) appears to reflect disease severity in pediatric patients with atopic dermatitis (AD). Our purpose was toexamine the relationship between time spent on treatment and parental psychological parameters such as anxiety and depression. Methods: TSOT was studied in a group of parents of patients with AD participating in an eczema school. TSOT included all types of topical treatment. In addition, dermatological life quality (the IDLQI questionnaire), depression (the MDI questionnaire), and anxiety (the STAI questionnaire) were assessed as well as the self-reported (by parent) disease severity, treatment effect, and confidence in treatment (VAS scales) using descriptive statistics, multiple linear regression, and rank correlations (Kendall's tau). Results: TSOT was found to be significantly associated with parental age (older parents report lower TSOT) and IDLQI (low quality of life with high TSOT), whereas all the other parameters appeared redundant. Sex of the parent showed no effect on TSOT. Conclusion: Our data suggest that TSOT is not correlated with anxiety ordepression. A positive independent correlation was found with general quality of life, offering mutual validation of the measures. The observations suggest that further investigation of TSOT as a surrogate measure of morbidityin AD may be of practical interest in order to develop an internationally comparable morbidity measure in AD.
Keywords: ankete; Anksioznost; Anxiety; Child; Depresija; Depression; Dermatitis atopični; Dermatitis, Atopic; kožne bolezni; Kvaliteta življenja; Otrok; Psychology; Quality Of Life; Questionnaires; therapy; zdravljenje